2003
DOI: 10.1034/j.1600-0773.2003.920105.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Salbutamol Differs between Asthmatic Patients and Healthy Volunteers

Abstract: Patients with asthma are a target group for medication with b2-agonists, often in combination with corticosteroids. Salbutamol is commonly marketed as racemate. R-Salbutamol carries b2-agonistic property whereas S-salbutamol does not. The racemate undergoes stereoselective sulphatisation by sulfotransferases mainly in the gut and liver, so that S-salbutamol rests for a longer time in the body and reaches higher plasma levels than R-salbutamol. Ten patients with mild stable asthma and at present without cortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
(17 reference statements)
0
10
0
1
Order By: Relevance
“…Thus, performance of longer trials is desirable to better discern the effects of (S)-albuterol under chronic conditions because it has been shown that severe asthma patients (who are more likely to use their racemic albuterol inhaler frequently) can have two to fi ve times higher levels of (S)-albuterol in their plasma [60]. Also, steroid-naïve asthma patients have high serum levels of (S)-albuterol compared with steroid-treated asthma patients and healthy volunteers [14,16], again perhaps because of issues related to control of asthma symptoms.…”
Section: Basic Human Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, performance of longer trials is desirable to better discern the effects of (S)-albuterol under chronic conditions because it has been shown that severe asthma patients (who are more likely to use their racemic albuterol inhaler frequently) can have two to fi ve times higher levels of (S)-albuterol in their plasma [60]. Also, steroid-naïve asthma patients have high serum levels of (S)-albuterol compared with steroid-treated asthma patients and healthy volunteers [14,16], again perhaps because of issues related to control of asthma symptoms.…”
Section: Basic Human Studiesmentioning
confidence: 97%
“…In this regard, one important characteristic of (S)-albuterol is its slower pharmacokinetic profi le (it is metabolized as much as 12 times slower than levalbuterol) [10,11]. This occurs in part because of its delayed sulfation and elimination by enzymes preferentially specifi c for levalbuterol [12][13][14][15], which results in differences in circulating levels of each isomer after administration of racemic albuterol [16]. It has been shown that circulating levalbuterol is undetectable within 2 to 3 hours after a single dose of inhaled racemic albuterol, whereas (S)-albuterol levels persist for as long as 12 hours and may be preferentially retained in the lungs [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is indeed of interest to note that the pharmacokinetics of ingested salbutamol was affected by the GR ligand, budesonide. The plasma concentrations of salbutamol were lowered significantly in patients after administration of budesonide and this was attributed to the changes in metabolism of salbutamol (Naidu Sjosward et al, 2003). Since salbutamol is metabolized exclusively by SULT1A3 to the inactive sulfate conjugate (Walle et al, 1993b), it is likely that induction of SULT1A3 activity by the GR ligand, budesonide led to increased metabolism and hence lowered plasma levels.…”
Section: Discussionmentioning
confidence: 98%
“…Кверцетин ингибирует сульфатирование R-сальбутамола, причем интенсивность ингибиторного действия на одиндва порядка выше в двенадцатиперстной кишке по сравнению с печенью (Pacifici, 2004). В результате S-сальбутамол более длительный период персистирует в организме и достигает значимо более высоких концентраций в плазме крови по сравнению с R-энантиомером (Sjöswärd et al, 2003). SULT1A3 относительно резистентен к ингибиторным эффектам мефенамовой кислоты, салициловой кислоты и кверцетина (Pacifici, 2004).…”
Section: фармакокинетикаunclassified